Improving Learning Outcomes Theme VII Sub Theme 1 Using the Problem-Based Learning Model for Fifth Grade Students at SD Negeri 2 Samigaluh, Kulon Progo Regency, Academic Year 2021/2022 - Suyanti (IJCER (International Journal of Chemistry Education Research), 2023)
This research aims to improve student learning outcomes in thematic subjects, theme VII, sub-theme 1, class V, SD Negeri 2 Samigaluh for the 2021/2022 academic year through applying the problem-based learning model. This type of research is Classroom Action Research conducted for two cycles, each consisting of 2 meetings. The subjects in this study were 13 students in class V SD Negeri 2 Samigaluh, Kulon Progo Regency. Data collection techniques in this study through observation. The research results show an increase in student learning outcomes, wherein the first cycle was 10.5 with an average percentage reaching 80.77%. Whereas in cycle II, the number of students who met the Minimum Completeness Criteria reached 13 with a percentage of 100%. When compared with the acquisition of the first cycle with the second cycle there is an increase of 19.23%. The results of the research data, show that there has been a significant increase so the researchers determined that the problem-based learning model can improve student learning outcomes. The application of the Problem-Based Learning model in theme VII sub-theme 1 subjects can improve teachers' abilities in carrying out Teaching and Learning Activities.